Bipolar disorder - A review of current knowledge - from etiology and diagnosis to treatment - Woźnica, Weronika; Dąbrowska, Julia; Białogłowski, Michał; Mazurek, Katarzyna; Gęborys, Anna; Wojcieszak, Maja; Matuszewska, Julia; Kutnik, Kacper; Maziarczyk, Alicja; Lambach, Jakub (Quality in Sport, 2026)
Introduction: Bipolar disorder is a chronic mental illness characterized by significant and often unpredictable changes in mood and energy levels. It is characterized by periods of mania or hypomania alternating with episodes of depression. Unfortunately, it often remains underdiagnosed and difficult to treat as it requires a comprehensive approach that combines pharmacological and non-pharmacological strategies tailored to the phase and severity of the illness. Aim of the study: The aim of this review is to summarize the latest knowledge related to bipolar disorder, including epidemiology, pathophysiology, clinical types, and risk factors. In particular, it focuses on diagnostic difficulties and appropriate treatment. Materials and methods: A comprehensive literature review was conducted using “PubMed”, Google Scholar and other databases. The following keywords were used: “bipolar disorder”, “mood stabilizers”, “lithium”,“antipsychotics”, “electroconvulsive therapy” Conclusions: Bipolar disorder is a severe but underdiagnosed mental illness that poses a therapeutic challenge. The etiology is multifactorial, and the incidence is the same in women and men. Treatment should include two main components: acute treatment of mood episodes and maintenance therapy. Current treatment strategies include mood stabilizers and antipsychotic medications. Nevertheless, lithium remains extremely important, as it is the only medication with proven anti-suicidal effects. Psychological interventions and electroconvulsive therapy may be valuable adjuncts. Further research is needed to optimize treatment and improve outcomes for patients with bipolar disorder.